2016
DOI: 10.1002/mdc3.12463
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of Gait in Parkinson's Disease: Its Pathophysiology and Pragmatic Approaches to Management

Abstract: View Supplementary Video 1 View Supplementary Video 2 View Supplementary Video 3 Background Freezing of gait (FOG) in Parkinson's disease (PD) is poorly understood; however, with the established understanding of basal ganglia function, its manifestations should be more easily interpretable. This review examines freezing of gait (FOG) from such a perspective. Methods A search of the MEDLINE and EMBASE databases from the year 2000 onward for review articles, focused on the pathophysiology of FOG, was used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…The phenomenon of gradual step to step reduction is termed sequence effect (SE), which may attribute to the inability of basal ganglia (BG) to provide timing cues and is believed to cause FOG in PD patients (11,12). Based on the defects of BG function and gait-control system, the concept of dual requirement of background step length reduction (manifestation of gait hypokinesia) and presence of SE can explain most of the freezing phenomenon in PD (13). Chee et al reported that FOG episodes were induced more frequently through voluntarily diminishing step length if a significant SE was co-existent in the PD patient (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of gradual step to step reduction is termed sequence effect (SE), which may attribute to the inability of basal ganglia (BG) to provide timing cues and is believed to cause FOG in PD patients (11,12). Based on the defects of BG function and gait-control system, the concept of dual requirement of background step length reduction (manifestation of gait hypokinesia) and presence of SE can explain most of the freezing phenomenon in PD (13). Chee et al reported that FOG episodes were induced more frequently through voluntarily diminishing step length if a significant SE was co-existent in the PD patient (14).…”
Section: Introductionmentioning
confidence: 99%
“…Chee et al reported that FOG episodes were induced more frequently through voluntarily diminishing step length if a significant SE was co-existent in the PD patient (14). Particularly, motor blocks will not occur in the absence of SE during walking (13).…”
Section: Introductionmentioning
confidence: 99%
“…They observed this phenomenon only in the older (> 70 years) group but not in the middle-aged group. It is unclear whether this phenomenon is a physiological characteristic of healthy aging or a pathological symptom of subtle diseases, such as those accompanied by gait freezing [24]. Second, the phenomenon of extended error correction time has not been reported in earlier studies with driving simulators, due probably to the function unique to PS-PVT that requires switching between parallel and cross modes every 2 min.…”
Section: Discussionmentioning
confidence: 97%
“…It was suggested that the impaired BG function in PD leads to abnormalities of motor set and motor cues and in consequence the initiation deficits and reduced step length. Such mechanism may be responsible for incidents of gait blocking [48]. So, NW can be considered as the kind of cueing in which upper limb movements are the source of external information enabling the normalization of speed and amplitude of leg movements while walking.…”
Section: Discussionmentioning
confidence: 99%